Filiform polyposis in the sigmoid colon: A case series - Lee, Chang Geun (The WJG Press and Baishideng, 2010)
Filiform polyposis is a rare condition of uncertain pathogenesis that is usually found in association with Crohn’s disease, ulcerative colitis, intestinal tuberculosis or histiocytosis X. We report seven interesting cases of polyposis with various pathologic components, mainly located in the left side of the colon with no associated inflammatory bowel disease, intestinal tuberculosis or histiocytosis X. Multiple finger-like polypoid lesions with the appearance of stalactites were noted on the left side of the colon, especially in the sigmoid area, at the time of colonoscopy. The polyps had a variety of sizes and shapes and were shown to have various histopathologic components among the different patients. Although filiform polyposis localized in the sigmoid colon appears not to have high oncogenic potential, periodic follow-up seems to be needed.